2019
DOI: 10.15835/buasvmcn-vm:2019.0003
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Extended β-Lactamases and Plasmid Mediated Quinolones Resistancein Escherichia Coli from Shelter Dogs

Abstract: The aim of this study was to determine the prevalence of β-lactamase (TEM, SHV, OXA), extended-spectrum β-lactamase (ESBL) and genes encoding plasmid mediated resistance to quinolones (PMQR) in extended spectrum cephalosporin (ESC)-resistant Escherichia coli isolated from dog faeces from two shelters in the North-East of Romania. Eighty-eight faecal samples from healthy dogs were analysed by cultivation on Brilliance ESBL medium (Oxoid, UK), followed by phenotipic ESBL screening using combination disc test (CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The estimated global prevalence of ESBL-producing E. coli in dogs is 6.29% [2] , and earlier studies from Brazil, Romania, and Japan have shown considerably higher proportions of ESBLproducing Enterobacteriaceae in sheltered and stray dogs, ranging from 14.6 to 31.0% [3][4][5] . Moreover, a recent project by the Finnish Food Authority revealed that the proportion of ESBL-producing En- terobacteriaceae was 30% amongst imported dogs, many of which had a stray or shelter background [6] .…”
Section: Introductionmentioning
confidence: 96%
“…The estimated global prevalence of ESBL-producing E. coli in dogs is 6.29% [2] , and earlier studies from Brazil, Romania, and Japan have shown considerably higher proportions of ESBLproducing Enterobacteriaceae in sheltered and stray dogs, ranging from 14.6 to 31.0% [3][4][5] . Moreover, a recent project by the Finnish Food Authority revealed that the proportion of ESBL-producing En- terobacteriaceae was 30% amongst imported dogs, many of which had a stray or shelter background [6] .…”
Section: Introductionmentioning
confidence: 96%